The encyclopedia of sexually transmitted diseases - Shoquist, Jennifer; Stafford, Diane (New York : Facts on File, 2004)
Presents approximately one thousand alphabetized entries on sexually transmitted diseases, covering the various types, preventive methods and treatments, laws and foundations, and other topics related to these illnesses, and includes an extensive bibliography and other references and resources
Includes bibliographical references (p. 283-302) and index
Keywords: Sexually transmitted diseases -- Encyclopedias; Sexually Transmitted Diseases; Encyclopedias